Review of Learning Disability and Everyday Life by Alex Cockain - Barden, Owen (My University, 2025)
Learning Disability and Everyday Life offers an account of Alex Cockain’s life with his brother Paul. Paul is a middle-aged man who has labels of autism and learning disability. The account is ethnographic in texture, and Cockain draws on an impressive array of theory relevant to disability studies including anthropology, sociology, linguistics, phenomenology and a good deal more. He also makes liberal use of disability studies literature in advancing his analysis and arguments. The book shows how apparently mundane moments and practices in Alex and Paul’s everyday lives are produced by the hegemonic forces which saturate our social world: D/discourses, power relations, normalcy, ableism and disablism, and so on. In other words, all the usual suspects are here, and they are used to illuminate not just Alex and Paul’s everyday lives, but the ways in which other people including neighbours, doctors, and Government bureaucrats respond to autism and learning disability, and people who carry such labels, in their everyday lives.
Learning Disability and Everyday Life
PUBLISHED
Keywords: Inclusive Society; Autistic Spectrum disorders; Intellectual Disability; Accessibility; Attitudes; Advocacy and political participation; Carers; Community; Communication; Home and community living; Relationships; Social exclusion